Élő Rádiókabaré. Tavaszi hadjárat - Salgótarján
K&H advertisement, Hócipő cabaret in Salgótarján, László Majláth-Mikes, László Juszt, András Bánó, Tivadar Farkasházy, Tibor Selmeczi, Mátyás Usztyics, György Nádas, András Nagy Bandó, István Éles, Imre Bajor, Sándor Fábry, Géza Boncz, advertisment